Integração da manufatura enxuta, seis sigma e teoria das restrições: um modelo conceitual incluindo sistemas de execução da manufatura e sistemas avançados de planejamento e programação - Costa, Bruno Alexandre Durães da (2014)
Studies about continuous improvement in industries are being conducted to optimize the resources used and maximize the financial performance of companies. The most widely used approaches to implementing these improvements in industry, in recent years, are: the theory of constraints, lean manufacturing and six sigma, with several studies using a hybrid solution instead of just one approach. Based on this, the present work aimed to propose a conceptual model based on the theoretical framework that integrates the three above approaches and using advanced systems of planning and control of production and manufacturing execution systems to plan and collect information from production. Thus, a systematic literature research in major research bases, in order to identify existing models of integration of the three approaches to continuous improvement and the main concepts of each philosophy was conducted. The research, theoretical-conceptual and exploratory in nature, it also proposed to present the key concepts related to lean manufacturing, theory of constraints, six sigma and prospects of integration envisaged in the literature. In the results the advantages of including Manufacturing execution systems and Advanced Planning Systems in the production models of integration were presented.